Antibiotic Types and Handling Practices in Disease Management among Pig Farms in Ashanti Region, Ghana. (11th September 2014) - Osei Sekyere, John
Abstract : Antibiotic resistance in bacteria is affected by the type of antibiotics used and how they are handled. The types of antibiotics used by 110 pig farms in the Ashanti region and the handling practices of the farmers during disease management were assessed. Injectable tetracycline, sulphadimidine, benzylpenicillin, and dihydrostreptomycin containing antibiotics were overly used by the farmers especially in the management of diarrhea, rashes, and coughs. Unsafe storage and disposal practices observed among the farms reflected the abysmal knowledge on appropriate use of antibiotics. Misdiagnosis and inadequate protection during antibiotic handling in the farms increased the risk of antibiotic resistance development and spread. The factors affecting antibiotic resistance development and spread are rife in pig farms in Ashanti region and appropriate education and veterinary interventions are needed to prevent resistant bacteria from becoming endemic in pork and pig farm communities.